Fordham, a history of the Jesuit University of New York : 1841-2003 - Shelley, Thomas J. (Libros electrónicos en Ebscohost, 2016)
Based largely on archival sources in the United States and Rome, this volume documents the evolution of Fordham from a small diocesan college into a major American Jesuit and Catholic university. It places the development of Fordham within the context of the massive expansion of Catholic higher education that took place in the United States in the twentieth century.